Fossil Hystricoidea from the Makapan Valley, Transvaal - Greenwood, Marjorie (Bernard Price Institute for Palaeontological Research, 1955)
In this paper are described three Hystricomorphs from the Australopithecus prometheus layer of the Makapan Valley Limeworks Quarry, Transvaal. Besides Hystrix cf. H.africae-australis, a new genus and species Xenohystrix crassidens and a new species Hystrix major are recognized.
Main article
Keywords: Hystricoidea, Australopithecus prometheus, Makapan valley, Transvaal